PERKEMBANGAN PERKEBUNAN TEH JOLOTIGO KECAMATAN TALUN KABUPATEN PEKALONGAN TAHUN 1957-1996 (PENGARUHNYA TERHADAP KEHIDUPAN SOSIAL EKONOMI) - Praharwati, Vika (Journal of Indonesian History, 2014)
Jolotigo tea plantation is one of the businesses managed by PTP. Nusantara IX (Persero) Annual Crops Division, which is one Enterprises (SOEs). PTP. Nusantara IX managing unit of tea gardens and 8 sugar mills spread throughout Central Java. Jolotigo tea plantations located between Talun District of Pekalongan and types of crops produced include coffee, tea, quinine and rubber.Â  At the time of the Dutch Government, Jolotigo plantation planted with coffee and deemed not suitable and replaced Tea, Kina, and rubber. At this time all the equipment was minimal and wear of equipment can help, even where pemetikannyapun away from the plant. The resulting tea is black tea and marketing only to Europe. At the Government of Japan are all cut off, thus reducing the income of the plantation economy. Dampakanya the Government of the Republic of Indonesia plantations under Administrator R. Soemardjo. In 1960 the factory was built, and administrators who first dirangkep be pimpimnan and cinder. Â